Achieving High Aspect Ratio of Track Length to Width in Molds for Discrete Track Recording Media. (8th June 2008) - Aung, K. O.; Shankaran, C.; Sbiaa, R.; Tan, E. L.; Wong, S. K.; Piramanayagam, S. N.
Abstract : Discrete track media (DTM) fabricated by nanoimprint lithography (NIL) is considered as a potential technology for future hard disk drives (HDD). In the fabrication of a master mold for NIL, patterning the resist tracks with a narrow distribution in the width is the first critical step. This paper reports the challenges involved in the fabrication of high aspect ratio discrete tracks on Polymethylmethacrylate (PMMA) resist by means of electron beam lithography. It was observed that fabrication parameters applied for successful patterning of discrete tracks in nanoscale length were not directly suitable for the patterning of discrete tracks in micron scale. Hence different approaches such as thick layer resist coating, introducing of post exposure baking process, and varying of exposure parameters were used in order to achieve uniform sharp discrete tracks in micron scale length on the resist. The optimal parameters were used to pattern 20 μ m long tracks with 70 nm track pitch on the resist.